Tratamento preferencial ao cliente na relação de mercado B2B: um estudo com fornecedores do setor farmacêutico no Brasil - Spadoto, Fábia Auxiliadora Pereira de Mattos (2018)
The supply chain management or value chain has always had its orientation aimed at generating more value for the final customer. A recurring phenomenon has been the reduction in the number of suppliers, as a consequence of economic changes in the market or even of a natural order, and which directly affects buyer-supplier relations: some companies are excluded from supply and others are preferred. Receiving preferential treatment in relation to other companies is a desire of many organizations, but there is the condition in this relationship, before supplier satisfaction occurs, and that is directly linked to the condition of being a preferred customer. The theoretical model addressed by Hüttinger et al. (2014) was used as the theoretical anchor in this study. This dissertation aimed to analyze the factors that induce suppliers to treat some customers more preferentially than others in B2B market relations and how this association between the determinants of customer attractiveness, supplier satisfaction and preferential customer status and its antecedents . The research in question was quantitative and descriptive. Data collection was done through an electronic survey with suppliers of direct materials from the same pharmaceutical industry in Brazil. The sample consisted of 84 participants, the instrument used was an online questionnaire already validated in Germany, which had its reliability of the new structuring measured with a Crombach Alfa of 0.967. Descriptive statistics, factorial analysis and regression were used as techniques. In the analysis of the determinants of preferential treatment to the customer, there are indications that customer attractiveness and supplier satisfaction were highlights in the perception of the suppliers researched. In the preferred customer status it was noticed that the suppliers have not yet given the customer the preferential customer status. It was possible to verify that growth opportunity, operational excellence, reliability and innovation potential are factors that induce suppliers to grant preferential treatment to the customer, which confirms that there were indications that the model suggested by Hüttinger et al. (2014) in much of it is compatible with the Brazilian sample